An Evaluation of Bureaucratic Barriers to Public Accountability in Regional Development: Implications for The Community Economy - Siti Nurjanah; Jopie Tommy Rompas; Maulana Irfan Andriansyah (Journal Research of Social Science, Economics, and Management, 2026)
This study aimed to analyze bureaucratic constraints on public accountability in regional development and their implications for community economic conditions. The research was based on the problem of limited bureaucratic effectiveness, characterized by hierarchical organizational structures, complex administrative procedures (red tape), and weak performance-oriented work cultures. This study employed a descriptive qualitative approach through a literature review using thematic analysis of academic and policy sources. The findings indicated that bureaucratic constraints significantly reduced public accountability, particularly in terms of transparency and performance accountability. This condition resulted in inefficiencies in regional development implementation, increased economic transaction costs, and declining public trust in local governments. The downstream impacts were reflected in weakened community economic competitiveness, particularly among Micro, Small, and Medium Enterprises (MSMEs), as well as reduced regional investment attractiveness. The study concluded that a consistent causal relationship existed among bureaucratic constraints, public accountability, development performance, and community economic conditions. Therefore, bureaucracy reform based on accountability principles, digital governance transformation, and strengthened oversight systems are essential prerequisites for improving regional development effectiveness.